Optimalisasi Peran KSPPS BMT Beringharjo KCP Dolopo dalam Meminimalisir Praktek Rentenir di Masyarakat - Reta Nurnalia; Ruliq Suryaningsih (Niqosiya: Journal of Economics and Business Research, 2023)
Baitul Maal wat Tamwil (BMT) is a microfinance institution that operates on Sharia principles/profit sharing, which has the aim of being able to grow micro-enterprises in order to elevate the degree and dignity and defend the interests of the poor. The research method used in this research is a qualitative method with a descriptive descriptive approach. With data collection techniques in the form of interviews and using descriptive qualitative analysis techniques. The conclusion of this study shows. The conclusions from this study show that optimizing the role of KSPPS BMT Beringharjo in minimizing the practice of moneylenders in the community is in accordance with Sudarsono's theory, but still needs improvement in efforts to distance the community from non-sharia economic practices such as providing outreach to the community.